Beyond Cronbach's alpha: rethinking reliability analysis in the age of digital learning - Libasin, Zuraira; Ahmad, Nurhafizah; Umar, Norazah (Unit Penerbitan JSKM, 2025)
Cronbach’s alpha has been widely used to measure internal consistency in educational research due to its simplicity and ease of interpretation. However, its assumptions, such as tau equivalence, unidimensionality, and equal item contribution, are often violated in modern digital learning environments. This paper examines the limitations of Cronbach’s alpha and presents alternative approaches that better suit technology enhanced assessments, namely McDonald’s omega, Generalizability Theory, and Item Response Theory. A practical framework is proposed to guide the selection of reliability methods based on assessment characteristics. Examples from quizzes, reflective writing, and gamified simulations illustrate how these methods address specific psychometric challenges in digital contexts. The study shows that aligning reliability techniques with assessment design improves measurement accuracy, supports adaptive feedback, and enhances transparency in reporting. It concludes that adopting modern reliability approaches and investing in methodological training are essential for creating fair and valid digital assessment practices in education.